The Role of Talent Management in Improving the Performance of Principals Mediated Intensively in Vocational or High School in Aceh - Chaidir; Marzuki; Akmal; Afrizal; Ijal Fahmi (Universitas Serambi Mekkah, 2024)
This research is an explanatory study that uses a qualitative approach in assessing the role of talent management in improving the performance of principals in high schools / vocational schools in Aceh, focusing on managerial skills, leadership, communication, and innovation. This research is based on a review of related literature involving an in-depth analysis of concepts related to talent management, talent identification, talent development, talent retention, performance measurement, organizational culture development, and the role of incentives as mediating elements. The results of this study provide deeper insight into the role of talent management in the context of education in Aceh and can be the basis for improving talent management policies and practices in an effort to improve the leadership quality of school principals in SMA/SMK.